Neonatal Resuscitation Training and Equipment in Private Health Institutions in Kano Metropolis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Over 200,000 babies die yearly in Nigeria, of which about 26% is due to birth asphyxia. Effective neonatal resuscitation (NR) using basic equipment is capable of preventing up to 30% of deaths associated with perinatal asphyxia. However, NR is only effective where caregivers have sufficient knowledge and required skills. The frequent industrial actions by health workers in the public sector have brought to the fore the importance of private health facilities in healthcare delivery. Thus, there is a need to assess training of health workers and availability of basic equipment in private health institutions in Kano.Aim:To assess availability of trained providers on NR and resuscitation equipment in private health facilities in Kano.Materials and Methods:This is a cross sectional survey of 85 conveniently sampled private institutions that provide obstetric care as part of their services in Kano metropolis. A semi-structured self-administered questionnaire was used to collect data from each facility.Results:Seventy eight filled questionnaires were retrieved and analyzed. There were 25 specialist clinics, 44 general practice facilities, and nine maternity homes/primary healthcare (PHC). Only 29 (37.2%) of the facilities have caregivers trained on NR in attendance during normal deliveries. Thirty four (43.5%) facilities have written protocol on NR. Only two (22.2%) of the maternity homes/PHC have functional ambu bags; the corresponding figures for specialist and general practice clinics are 16 (64%) and 24 (54.5%) respectively.Conclusion:There is insufficient number of trained personnel on newborn resuscitation, and low availability of newborn resuscitation equipment in private health institutions in Kano metropolis.